Penggunaan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SDN 04 Muaro Paiti - Arsiska, Nelvi (Universitas Sebelas Maret, 2020)
Talking about education issues, it will not be separated from the learning process in the classroom. Science learning is a human effort in understanding the universe through precise observations on the target, and using the right procedures, and explained with valid reasoning so that the correct conclusions are produced. PBL (Problem Based Learning) is a learning model that accommodates student involvement in authentic learning and problem solving. The application of the PBL learning model to the fifth grade science subject at SDN 04 Muaro Paiti based on the results of research conducted by PBL model researchers can improve student learning outcomes by using several steps. In the PBL model, the teacher acts as a facilitator to guide learning, and students become the main learning center. The application of the PBL learning model can improve science learning outcomes for class V SDN 04 Muaro Paiti, both cognitive, affective, psychomotor earning outcomes.